A step toward sustainability, dignity, and good health through Noraa. Issue 2 (3rd April 2021) - Vig, Shinu
ABSTRACT: Sustainable entrepreneurs can play an important role in the 2030 Agenda for Sustainable Development, adopted by the United Nations in 2015, by promoting inclusive economic development, generating income and employment opportunities, and protecting our planet. The sustainable enterprises that are categorized as micro-, small, and medium-sized enterprises (MSMEs) may be small in size, but their impact is crucial for the local areas where they operate. This article discusses the case of Noraa, a micro-enterprise in India, which is making an important contribution to the achievement of the Sustainable Development Goals by taking care of both people and the planet. Noraa is a sustainable enterprise run by two young entrepreneurs. It provides a range of organic and biodegradable sanitary pads and is committed to the cause of the environment and menstrual hygiene.